Interdisciplinary studies of «new researchers» on Ricardo Palma’s Peruvian Traditions - Flores Heredia, Gladys (2023)
The Peruvian Traditions, Ricardo Palma’s masterpiece, has been the subject of study by literary critics, both historiographical and analytical. Some approaches from the field of literary studies have connected the life and the work, and other approaches have explained the stylistic features and the use of ironic forms. But the Palmian traditions are also substantially important because they represent diverse processes related to the knowledge they provide about architecture, engineering, psychology, medicine and other fields of knowledge. In this text we offer an analytical mapping of a set of articles by «new researchers» that were published in the indexed journal El Palma de la Juventud. Revista de Estudiantes de la Universidad Ricardo Palma (n.o 1, 2019; n.o 2, 2020; and n.o 3, 2021); we consider that these reflexive enquiries call attention to the need to fill that cognitive gap. In this sense, the object of our study is metacritical, i.e. we explain the different interdisciplinary approaches of these articles, as well as reconstruct the ideas and arguments concerning the Palmian traditions. In this way we systematize a picture as an argumentative mosaic of the main interdisciplinary approaches to the traditions in this second decade of the 21st century, a picture of the need to enrich the approaches of literary criticism with the participation of other disciplines in order to understand other possibilities for the production of meaning from the Peruvian Traditions.